APLIKASI KULIT BUAH MANGGIS (Garcinia mangostana L.) SEBAGAI PEWARNA ALAMI PADA KAIN KATUN SECARA PRE-MORDANTING - Manurung, Manuntun (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 2 Juli 2012)
The research about utilization of mangosteen skin as a natural dies on cotton by pre-mordanting methods with 1% (w/v) of lime water. The physical and chemical properties of the natural dies were tested using 1% w/v of detergent. The extraction of natural dye was conducted by heating in water with ratio 1:20 w/v for one hour. The results showed that the optimum mass of natural dye was adsorbed about 0.0402 g without mordant  and the colour was light brown.The pre-mordanting method gives optimum mass of natural dyes adsorbed of  0.0637 g, which with reddish brwon color. The color was brighter and more resistant to detergent solution.
Keywords: mangosteen, natural dye, pre-mordanting, cotton